Genetic Differentiation of Abies alba Outside Its Main Range Under Warm Meso‐ and Sub‐Mediterranean Conditions in Italy and Switzerland - Sevil Coşgun; Jérémy Gauthier; Giuliano Bonanomi; Gabriele Carraro; Paolo Cherubini; Marco Conedera; Erika Gobet; Maria‐Chiara Manetti; Gianluigi Mazza; Christoph Schwörer; Christoph Sperisen; Nadir Alvarez; et al. (Ecology and Evolution, 2025)
ABSTRACT Abies alba is an important European tree species currently mostly found at cool and humid sites in the montane zone. In the past, it grew under markedly warmer and drier climates during the Eemian and mid‐Holocene, and cryptic Mediterranean populations confirm the species' capacity to grow under warm, summer‐dry conditions. However, it is unknown if warm‐loving Mediterranean occurrences are related to specific genetic properties (e.g., subspecies or ecotypes). Investigating the genetics of cryptic warm‐loving populations is crucial for a better understanding of past and future population dynamics of A. alba. We genotyped 478 A. alba samples at 174 single‐nucleotide polymorphisms (SNP), covering a broad latitudinal range from Southern Italy to Switzerland while accounting for local altitudinal gradients, and combined these newly introduced genotypes with those of other European Abies populations from the literature. Population genetic structure analyses grouped the warm‐loving meso‐ and sub‐Mediterranean populations into the same genetic cluster as the mountain populations of each region. The occurrence of three genetic clusters from Northern to Southern Italy is in line with the glacial refugia history. The inferred evolutionary and demographic history suggests a northward expansion of A. alba after glaciation, as well as a trans‐Adriatic gene flow between Balkan and Southern Italian populations. Collectively, the combined genotypic data from individuals across the species' range demonstrate that cryptic Mediterranean populations of A. alba align with the local and large‐scale genetic structure of populations from its main range, suggesting that the species is able to thrive in a warmer and drier environmental range than hitherto anticipated. This finding implies that it is unneeded to postulate extinct subspecies or ecotypes to explain the occurrence of meso‐ and sub‐Mediterranean Eemian or mid‐Holocene silver fir forests, with important implications for future A. alba population dynamics.